Analisis Biaya dan Pemilihan Peminatan Terhadap Ketertarikan Mahasiswa Dalam Program Food and Beverage Service - Fajar Pramono; Sri Marini (Program Studi Administrasi Bisnis, 2024)
The decline in the number of students in the food and beverage service is a concern for AKPAR NHI Bandung. The number of students in the program is not on target and is thought to be closely related to tuition fees and major selection. Cost can be a problem for prospective students to choose the specialization of the food and beverage service program and have a big impact on interest in choosing the program. The formulation of this research problem is how students' interest in choosing food and beverage service specialization and how the cost of education programs. The purpose of this study was to determine the impact of fees and specialization selection and to determine how much impact fees and specialization selection have on student interest in food beverage service. The population in this study were students with a sample size of 60 respondents to provide information about interest in choosing a college program. The data analysis technique used in this research is quantitative data analysis where the research analysis method uses path analysis to analyze the research results. The results showed that the specialization selection variable had a greater influence on student interest than the cost variable.